Lifeworld: socio-environmental influence on crack cocaine use by teenagers - Marina Soares Mota; Giovana Calcagno Gomes; Juliane Portella Ribeiro; Adriane Maria Netto de Oliveira; Aline Campelo Pintanel; Simone Quadros Alvarez
ABSTRACT Objective: To understand the influence of the lifeworld on crack cocaine use by teenagers undergoing treatment at the Psychosocial Care Center for users of alcohol and other drugs. Method: Qualitative research carried out with thirteen teenagers attended at the Psychosocial Care Center for users of alcohol and other drugs, from a municipality in the South of Brazil. The data were collected through semi-structured interviews and the Comprehensive Analysis was carried out from the Phenomenology of the Social World of Alfred Schütz. Results: In the lifeworld, there is influence of the community to which the teenager belongs; of the family, by the excess of permissibility and being in an environment of drug use and violence; and the school, where it is influenced by individuals to consume them. Conclusion: Elements from the lifeworld influence the teenager for the consumption of crack cocaine, being necessary actions contextualized with their world of life.